tert-Butyl Peroxybenzoate Mediated Selective and Mild N-Benzoylation of Ammonia/Amines under Catalyst- and Solvent-Free Conditions - Yadav, Dilip Kumar T.; Bhanage, Bhalchandra M. (Synlett, 2015)
A new protocol for the synthesis of amides from tert-butyl peroxybenzoate (TBPB) and ammonia/amines has been developed under catalyst- and solvent-free conditions. The ammonia, primary and secondary amines reacted smoothly with TBPB to furnish the corresponding primary, secondary, and tertiary amides in excellent yields. TBPB proved to be an efficient and highly chemoselective benzoylating reagent for aliphatic amines in the presence of aromatic amines/ hydroxyl groups.
Keywords: tert-butyl peroxybenzoate; N-benzoylation; catalyst-free; solvent-free; amides